Myeloid-derived NF-κB negative regulation of PU.1 and c/EBP-β-driven pro-inflammatory cytokine production restrains LPS-induced shock. Issue 2 (February 2017) - Vanoni, Simone; Tsai, Yi-Ting; Waddell, Amanda; Waggoner, Lisa; Klarquist, Jared; Divanovic, Senad; Hoebe, Kasper; Steinbrecher, Kris A; Hogan, Simon P
Sepsis is a life-threatening event predominantly caused by Gram-negative bacteria. Bacterial infection causes a pronounced macrophage (MΦ) and dendritic cell activation that leads to excessive pro-inflammatory cytokine IL-1β, IL-6 and TNF-α production (cytokine storm), resulting in endotoxic shock. Previous experimental studies have revealed that inhibiting NF-κB signaling ameliorates disease symptoms; however, the contribution of myeloid p65 in endotoxic shock remains elusive. In this study, we demonstrate increased mortality in mice lacking p65 in the myeloid lineage (p65 Δmye ) compared with wild type mice upon ultra-pure LPS challenge. We show that increased susceptibility to LPS-induced shock was associated with elevated serum level of IL-1β and IL-6. Mechanistic analyses revealed that LPS-induced pro-inflammatory cytokine production was ameliorated in p65-deficient bone marrow-derived MΦs; however, p65-deficient 'activated' peritoneal MΦs exhibited elevated IL-1β and IL-6. We show that the elevated pro-inflammatory cytokine secretion was due, in part, to increased accumulation of IL-1β mRNA and protein in activated inflammatory MΦs. The increased IL-1β was linked with heightened binding of PU.1 and CCAAT/enhancer binding protein-β to Il1b and Il6 promoters in activated inflammatory MΦs. Our data provide insight into a role for NF-κB in the negative regulation of pro-inflammatory cytokines in myeloid cells.